Successful surgical repair of a full-thickness intramuscular muscle belly rupture of pectoralis major - Green, Chadwick; Wang, Allan; Henderson, Jon; Ebert, Jay; Edwards, Peter (Elsevier, 2019)
Pectoralis major (PM) tendon ruptures are well documented in the literature; however, PM full-thickness intramuscular rupture of the muscle belly is rare, with only 6 other cases reported to date.1,3,4,6,16,17 Five of the 6 cases were surgically repaired. Four of these reported good to excellent results,3,16,17 based on the Bak Criteria,3 though they did not include both pre- and postoperative magnetic resonance imaging (MRI) or assess other outcome measures such as high-level functional tests. One case was treated conservatively and did not achieve an “excellent” outcome17; however, the exact outcome was not specifically reported. We present the only case to our knowledge with pre- and postoperative MRI, Bak Criteria assessment, and postoperative PM-specific functional testing—including isokinetic dynamometer strength, maximal arm active range of motion, and functional scores.